(untitled) (Editora Impacto Científico, 2025)
Suicidal ideation is considered one of the most serious psychiatric emergencies, characterized by immediate risk of death, intense psychological distress, and high social vulnerability. Emergency care is often the first point of contact for patients in crisis with health services, and a rapid and appropriate response from staff can be decisive in saving lives. The approach must be multidimensional, encompassing clinical, psychiatric, social, and ethical assessment, ensuring both the preservation of life and respect for the individual’s dignity. In this chapter, we will discuss the main aspects of managing suicidal ideation in emergency care, organized into eight topics ranging from initial screening to coordination with public prevention policies.